EXPLORING STUDENTS’ EXPERIENCES USING ENGLISH SONGS TO ENHANCE VOCABULARY MASTERY IN VOCATIONAL HIGH SCHOOL - Risti Ayu Iriani Pudjono; Arso Setyaji; Siti Nur'Aini (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2026)
For many years, English vocabulary teaching in vocational high schools has been a widespread and persistent problem plaguing English teachers in the field. Taking the classroom conditions of XI-grade students majoring in Institutional Accounting and Finance at SMK Perdana Semarang as an example, the traditional vocabulary-teaching model, which relies on memorizing word lists and repetitive written assignments, has led to two core problems: low student participation in class and poor vocabulary retention. This study uses English songs as an alternative teaching medium. Adopting a qualitative descriptive method, drawing on classroom experiences in the school, and conducting an analysis along three dimensions: student motivation, participation level, and vocabulary retention level. Supported by Krashen’s Affective Filter Hypothesis, the Nation’s Vocabulary Knowledge Framework, and Kolb’s Experiential Learning Theory, and combined with verified conclusions from previous research, which states that song-based teaching that combines appropriately selected songs with integrated structured activities can create a relaxed classroom, increase pronunciation awareness, and strengthen long-term vocabulary retention. This study proposes that music-integrated teaching is a formal strategy that aligns with the logic of teaching. These strategies are available for English teachers in vocational schools to adopt to achieve effective, contextually relevant, and student-centered vocabulary instruction.